2012
DOI: 10.1097/psy.0b013e318244903f
|View full text |Cite
|
Sign up to set email alerts
|

Optimism, Response to Treatment of Depression, and Rehospitalization After Coronary Artery Bypass Graft Surgery

Abstract: Objective Optimism has been associated with a lower risk of rehospitalization after coronary artery bypass graft (CABG) surgery, but little is known about how optimism affects treatment of depression in post-CABG patients. Methods Using data from a collaborative care intervention trial for post-CABG depression, we conducted exploratory post hoc analyses of 284 depressed post-CABG patients (2-week posthospitalization score in the 9-item Patient Health Questionnaire ≥10) and 146 controls without depression who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 44 publications
2
53
1
1
Order By: Relevance
“…Consistent with past findings in studies of optimism in adults (e.g. Hart, Vella, & Mohr, 2008;Scheier et al, 1994;Tindle et al, 2012), The Journal of Positive Psychology 407 our correlational results indicated that greater pessimism (lower optimism) was associated with greater depressive symptoms in primary care patients. Likewise, consistent with past findings in studies of hope in adults (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with past findings in studies of optimism in adults (e.g. Hart, Vella, & Mohr, 2008;Scheier et al, 1994;Tindle et al, 2012), The Journal of Positive Psychology 407 our correlational results indicated that greater pessimism (lower optimism) was associated with greater depressive symptoms in primary care patients. Likewise, consistent with past findings in studies of hope in adults (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…In turn, negative emotions may translate to poor appraisals of well-being. A recent study supports this idea: optimistic patients treated with coronary artery bypass graft scored higher than pessimists on psychological health status appraisals, and this difference was most pronounced in patients categorized as depressed according to PHQ-9 scores (Tindle et al, 2012). Furthermore, longitudinal research suggests that optimism predicts mental health-related quality of life over time, and that the effects of optimism and depressive symptoms on quality of life are independent (Achat et al, 2000).…”
Section: Discussionmentioning
confidence: 85%
“…Compared with pessimists, optimists had lower rates of rehospitalisation. 21 The Finnish Happiness-Flourishing Study (FHFS) is a national effort to promote positive mental health and positive health-related behaviour in the Finnish population. The aim of this study was to explore how one dimension of optimism, that is, high confidence in the future, is related to health-related behaviours and whether current socioeconomical status and psychological distress contribute to these relations in a large web-based sample of 101 257 Finns aged 18 and above.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%